Time-of-day influences resting-state functional cortical connectivity - Iester, Costanza; Biggio, Monica; Cutini, Simone; Brigadoi, Sabrina; Papaxanthis, Charalambos; Brichetto, Giampaolo; Bove, Marco; Bonzano, Laura (Frontiers in Neuroscience, 2023)
Time-of-day is rarely considered during experimental protocols investigating motor behavior and neural activity. The goal of this work was to investigate differences in functional cortical connectivity at rest linked to the time of the day using functional Near-Infrared Spectroscopy (fNIRS). Since resting-state brain is shown to be a succession of cognitive, emotional, perceptual, and motor processes that can be both conscious and nonconscious, we studied self-generated thought with the goal to help in understanding brain dynamics. We used the New-York Cognition Questionnaire (NYC-Q) for retrospective introspection to explore a possible relationship between the ongoing experience and the brain at resting-state to gather information about the overall ongoing experience of subjects. We found differences in resting-state functional connectivity in the inter-hemispheric parietal cortices, which was significantly greater in the morning than in the afternoon, whilst the intra-hemispheric fronto-parietal functional connectivity was significantly greater in the afternoon than in the morning. When we administered the NYC-Q we found that the score of the question 27 (“During RS acquisition my thoughts were like a television program or film”) was significantly greater in the afternoon with respect to the morning. High scores in question 27 point to a form of thought based on an imagery dimension. It is conceivable to think that the unique relationship found between NYC-Q question 27 and the fronto-parietal functional connectivity might be related to a mental imagery process during resting-state in the afternoon.